Fast and global authenticity screening of honey using 1H-NMR profiling. (15th December 2015) - Spiteri, Marc; Jamin, Eric; Thomas, Freddy; Rebours, Agathe; Lees, Michèle; Rogers, Karyne M.; Rutledge, Douglas N.
Highlights: A worldwide collection of more than 800 authentic honeys were analyzed through NMR. Patterns of sugar addition in commercial honeys were identified. Determination of botanical origin is possible, with example of manuka honey. The methodology can be implemented for routine use in food control laboratories. Abstract: An innovative analytical approach was developed to tackle the most common adulterations and quality deviations in honey. Using proton-NMR profiling coupled to suitable quantification procedures and statistical models, analytical criteria were defined to check the authenticity of both mono- and multi-floral honey. The reference data set used was a worldwide collection of more than 800 honeys, covering most of the economically significant botanical and geographical origins. Typical plant nectar markers can be used to check monofloral honey labeling. Spectral patterns and natural variability were established for multifloral honeys, and marker signals for sugar syrups were identified by statistical comparison with a commercial dataset of ca . 200 honeys. Although the results are qualitative, spiking experiments have confirmed the ability of the method to detect sugar addition down to 10% levels in favorable cases. Within the same NMR experiments, quantification of glucose, fructose, sucrose and 5-HMF (regulated parameters) was performed. Finally markers showing the onset of fermentation are described.